Exergy based performance analysis of rice husk fuelled producer gas operated boiler for thermal application in parboiling mills. (1st April 2022) - Beno Wincy, W.; Edwin, M.; Arunachalam, U.; Joseph Sekhar, S.
Graphical abstract: Highlights: Exergetic performance of the producer gas fired boiler operated with rice husk powered gasifier was investigated. The exergetic performance was analysed for different equivalence ratios and reference temperatures. The exergetic efficiency of the components is in the order of Heat exchanger > Combustor > overall boiler system. The Potential Improvement is minimum and the Sustainability Index is maximum at the equivalence ratio of 0.2. Abstract: The utilization of rice husk to generate produce gas and run gas-fired boiler can enhance the overall efficiency of the rice parboiling system. Moreover, the exergy analysis of such a system maximizes the efficiency and helps to reduce the fuel requirement and environmental impact. To perform the exergy analysis in paddy parboiling mills, the properties of producer gas, air inflow to the combustor, water, steam, and flue gas must be needed. In this study, experiments are conducted to find these parameters and the exergetic performance has been analysed for different reference temperatures. 3D plots relating the important paraments are used to predict the performance of the boiler and its components. The exergy destruction is maximum at the combustor which is 65.5 %. The maximum exergetic efficiency achieved at the combustor, steam generator, and the total system is 33.45 %, 40.29 %, and 17.64 % respectively when the Equivalence Ratio (ER) of the gasifier is at 0.2. Whereas, the Potential Improvement is found to be a minimum of 49.21 kW and the Sustainability Index is a maximum of 1.21. The exergy efficiency of the boiler, heat exchanger, and combustor are found to be decreased up to 36.9 %, 21.06 %, and 29 % respectively when the reference temperature is increased from 280 K to 320 K.